Willingness-to-pay per quality-adjusted life year of patients with psoriasis: A study in Vietnam - Hang, Nguyen Thuy; Yen, Dinh Hoang; Hao, Nguyen Trong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: The chronic nature and frequent recurrence of psoriasis reduce patients' quality of life and increase treatment costs. This study aimed to estimate the willingness-to-pay (WTP) per quality-adjusted life-year (QALY) of psoriasis patients in Vietnam. Patients and methods: A cross-sectional study was conducted based on face-to-face interviews with psoriasis patients at Ho Chi Minh City (HCMC) Hospital of Dermato-Venereology. The Euro Quality of Life 5-Dimension 5-Level (EQ-5D-5L) questionnaire was used, and questions about WTP were asked. Factors related to WTP per QALY were analysed statistically. Results: A total of 310 psoriasis patients (58.4% males; mean age of 48.84±16.27 years) were included. The mean disease and treatment durations were 11.51±9.82 and 9.69±8.87 years, respectively. The mean health-related quality of life was 0.787±0.128, and WTP/QALY was 7,726.86±4,506.82 USD (179,100,000±104,463,500 VND). Patients with university/college degrees had a significantly higher WTP/QALY (10,666.60 USD - 247.24 million VND) than patients with high school or under high school education (8,440.44 and 6,638.38 USD - 195.64 million and 153.87 million VND, p<0.05). There was a significant negative correlation between WTP/QALY and age (r=-0.247, p=0.000). Conclusions: The WTP per QALY of psoriasis patients was almost 3 times higher than GDP per capita of Vietnam in 2018. Education level, health-related quality of life and age are associated with WTP/QALY.